Impact of consumer awareness on switching behavior in banking - Tomasz Szopiński (Contemporary Economics, 2021)
In the era of open banking, the phenomenon of bank switching will intensify. The aim of the current study is to answer the following question: is switching, or not switching banks, a result of conscious and independent decision-making? The results from primary data demonstrate that the switching group clients are more conscious than non-switching group clients. They are more likely to compare offers from different banks, visit blogs about finances, demonstrate independence in making financial decisions, and use more service providers which improves their knowledge concerning the offers. The analysis of perceptual maps shows that the switching group is differentiated by various switching costs.
Keywords: D14; G21; 330; Switching behavior; banking; switching costs; bank switching; financial decisions